THE NATIONAL CREDIT ACT: NEW PARAMETERS FOR THE GRANTING OF CREDIT IN SOUTH AFRICA - Stéfan Renke; Melanie Roestoff; Franciscus Haupt (Obiter, 2022)
The National Credit Act, which repeals and replaces the Credit Agreements Act and the Usury Act, has been assented to by the President on 10 March 2006. The Act is designed to prohibit certain unfair credit and credit marketing practices and to protectconsumers. A further objective is to promote responsible credit granting and use. The Act therefore prohibits reckless credit granting, regulates credit information and also provides for debt-reorganisation in cases of over-indebtedness by consumers. The purpose of this article is to provide an overview of the provisions of the Act and at the same time to provide an explanation of, and a commentary on the provisions discussed. In conclusion it is suggested that the Act introduces extensive changes to South African consumer credit law and that participants in the South African consumer credit market will have to review their credit practices and documentation to ensure compliance. Moreover, the Act sets out new parameters for the granting of credit as credit providers will in future have to assess a consumer’s credit worthiness before granting credit. It is pointed out that the Act has a wide field of application as it applies to a far greater number of contracts than the repealed legislation. Except for the few transactions specifically excluded from its ambit, the Act applies to all credit agreements irrespective of the type of movable goods or the amount of money involved. Consequently a large group of consumers, including the low-income consumers, will enjoy the protection of the Act. It is our submission that the Act will result in improved consumer protection, especially with regard to certain areas where protection of the consumer was lacking.We suggest that the success of the Act in practice depends on effective enforcement thereof and on consumer education. On the negative side we feel that the legislature perhaps tries to over-regulate the credit industry.